Volatile chlorinated hydrocarbons in antarctic superficial snow sampled during Italian ITASE expeditions - ZOCCOLILLO, Lelio; INSOGNA, SUSANNA; Luca Amendola; Claudia Cafaro (Chemosphere, 2007)
In order to detect the presence of some volatile chlorinated hydrocarbons (VCHCs) and to understand their transport and deposition mechanism, superficial snow was sampled during two Italian ITASE (International Trans Antarctic Scientific Expedition) expeditions: the first traverse was carried out in 1998/1999 from Terra Nova Bay to Dome Concordia; the second traverse was carried out in 2001/2002 through Adélie, George V, Oates and Northern Victoria Lands. Some VCHCs (chloroform; 1,1,1-trichloroethane; tetrachloromethane; 1,1,2-trichloroethylene; tetrachloroethylene) were analysed using a highly sensitive and selective hyphenated technique composed of a purge-and-trap injector coupled to a gas chromatograph with a mass spectrometric detector (PTI-GC-MS) operating in SIM mode. Investigated VCHCs were present in all analysed snow samples with concentration levels of several units, tens, or sometimes hundreds of ng kg-1. VCHC snow concentration levels remained approximately constant with changing distance from the coast and the comparison between fresh and aged snow did not show any substantial differences; on the basis of this evidence marine aerosol and dry deposition may be rejected as principal VCHC transport and deposition mechanism hypotheses. VCHC concentration levels in Antarctic snow samples were comparable to or greater than those found in snow from temperate zones. © 2006 Elsevier Ltd. All rights reserved.